The Living Dead of George Romero and Steven Spielberg: America, the Holocaust and the Figure of the Zombie. Issue 1 (2nd January 2017) - Graebner, William
Abstract : Recent scholarship has demonstrated that there was no postwar communal culture of silence among American Jews with regard to the Holocaust. Nonetheless, Americans, and Hollywood's filmmakers, were reluctant to engage and present the most horrific aspects of the Nazi death camps, including the barbarous treatment of camp inmates and the obscenities of the gas chambers, unmarked mass graves and incineration. By the late 1960s, however, a subset of Americans was beginning to come to terms with the traumatic memory of the Holocaust in a most unusual, indirect way: through films about zombies, the 'living dead' of cinema, featured in George Romero's now-famous trilogy – Night of the Living Dead (1968), Dawn of the Dead (1978) and Day of the Dead (1985) – and, less obviously, in Steven Spielberg's Poltergeist (1982). Romero's zombie – lacking emotion and affect as well as consciousness, locked in a present bereft of past and future, driven by the most primitive instincts of survival – resembles the Muselmänner, the 'living dead' of the concentration camps, existing in the state that Italian philosopher Giorgio Agamben calls 'bare life.' The Romero trilogy and Poltergeist also deal significantly with how zombies – and, by analogy, camp inmates, are treated in 'life' and in death. Both are victims: victims, for Spielberg, of desecration, their graves ignored or destroyed at the whim of a real-estate developer; victims, for Romero, of a shocking disregard for human dignity, and blatant disregard, too, for the traditions and rituals associated with death, including a proper burial and the naming of the dead.